Penerapan Jaringan Komputer Berbasis Mikrotik pada SMA N 1 Ulu Musi - Robert Ronaldo; Hendri Alamsyah; Yessi Mardiana (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Information and Communication Technology (ICT) has become a vital need in the world of education. SMAN 1 Ulu Musi faces the problem of suboptimal network infrastructure, particularly related to internet access and bandwidth management. The existing network is only a limited LAN without an internet connection. This study aims to design and implement a MikroTik-based computer network at SMAN 1 Ulu Musi to improve the quality of network services, perform fair bandwidth management, and support learning activities that utilize information technology. The method used is the Network Development Life Cycle (NDLC) which includes the stages of analysis, design, prototype simulation, implementation, monitoring, and management. The system implementation uses a MikroTik RB941 router connected to a 4G modem as the internet source. The implementation of the Mikrotik-based network succeeded in improving the stability and efficiency of internet access at SMAN 1 Ulu Musi. Before the implementation of the simple queue bandwidth, each client obtained 60 MBPS; after the simple queue was implemented to distribute bandwidth evenly, each client received a maximum allocation of 4 MBPS. QoS testing results showed good network performance: throughput of 0.6 KBPS, average delay of 0.866 seconds, jitter of 0.25 seconds, and packet loss of 0%. All client devices could connect and access the internet stably without significant disruptions. The implementation of a MikroTik-based computer network proved effective in improving the quality of network services at SMAN 1 Ulu Musi. This system succeeded in creating a network that is stable, manageable, and supports equitable internet access for learning activities.